Hypoparathyroidism in children and adolescents (part 2) - V. V. Smirnov; P. N. Vladimirova (Лечащий Врач)
The article considers modern data on etiology, pathogenesis, clinical picture, genetic diagnostics of hypoparathyroidism in adolescents and children. The syndromes flowing with the clinical picture of this disease are described. The methods of examination and modern recommendations for treatment are presented.